Does Human Capital Investment Matter to Inclusive Growth? - Ni Putu Sintha Devi Yogandhi; Gede Andika (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This research addresses the disparity between economic growth and inclusive welfare in Indonesia by examining the link between investment in human capital and inclusive economic growth. Despite economic expansion, the country hasn't witnessed proportional improvements in poverty, unemployment, and inequality. Employing quantitative methods and a time frame spanning 2000-2020, this study analyzes data on economic growth, education and health financing, and the Human Development Index. Findings reveal a nuanced relationship: while physical capital's impact on economic growth remains insignificant, human capital investment correlates significantly yet negatively with the quality of human capital per economic growth unit. Health sector financing positively influences economic growth, whereas education financing shows a negative impact. Notably, improvements in human capital and health financing significantly enhance economic inclusiveness, indicating their pivotal role in fostering inclusive economic growth in Indonesia in alignment with the Sustainable Development Goals.